Melatonin reduces astrogliosis in the hippocampus and cortex and cognitive deficits of streptozotocin-induced diabetic rats. - Nedzvetskii, V. S.; Baydas, G.; Kirichenko, S. V. (Lippincott Williams & Wilkins, 2006)
[Abstract Not Available]
Workshop of the European-Behavioural-Pharmacology-Society on Neurodegeneration - Basic Mechanisms of Motor and Cognitive Dysfunctions -- SEP 02-04, 2006 -- Cracow, POLAND